Role of High Resolution Computed Tomography in Characterization of Interstitial Lung Disease in Rural Tertiary Care Centre - Y. Ravi Kumar; P Jenikar; M. Sanjeev Kumar (Asian Journal of Medical Radiological Research, 2021)
Background: The Interstitial lung disease (ILD) are a group of diffuse parenchymal lung diseases that share many features but are sufficiently different from one another to be designated as separate disease entities. HRCT (High Resolution Computed Tomography) is particularly helpful in and diagnosing and characterizing these entities. Subjects and Methods: Data for the study collected from patients clinically suspected to have interstitial lung disease. Sample size: 31 patients. Study period: 2yrs. Study design: Prospective and Observational study. Inclusion criteria: Suspected cases of diffuse parenchymal lung disease by clinical history, physical examination, radiographic findings and appropriate laboratory investigations. Cases of all age groups irrespective of sex. Exclusion criteria: Known cases of lung malignancies and previously treated cases  of diffuse parenchymal lung disease are excluded from the study. Results: In a period of 2yrs study, 31 patients were diagnosed as ILDs on HRCT chest imaging. Among 31 cases most of them were IPF/UIP (35%), followed by AIP (16%). Honey combing is predominantly confined to UIP/IPF (100%), Traction bronchiectasis is predominantly seen in UIP/IPF (68%), Ground glass opacity is mostly seen in NSIP (23%) followed by AIP. Reticular opacities are predominantly seen in UIP/IPF (45%) followed by NSIP (18%). Consolidation is predominantly seen in HP (30%) and COP (30%). Septal thickening is predominantly seen in UIP/IPF (45%) followed by NSIP (18%). Conclusion: HRCT is the most sensitive tool for non-invasive imaging of the lung parenchyma in patients with suspected ILD.